Layʻ tī Paṇḍita Cha rā Ūʺ Moṅʻ Krīʺ (Mahā Vijjā) cu choṅʻ phre chui reʹ sāʺ saññʻ Kunʻʺ bhoṅʻ khetʻ suta ratanā khoʻ chui thuikʻ so Rheʺ boṅʻ kabyā poṅʻ khyupʻ (Paññā ʼA laṅʻʺ pra Cā ʼupʻ Tuikʻ, 1962)
Collection of poems of the Konbaung period; includes commentaries.